Uplift-restraining Friction Pendulum seismic isolation system. - Roussis, Panayiotis C. (Earthquake engineering & structural dynamics.)
This paper extends the scope of seismic isolation by introducing an innovative uplift-restraining Friction Pendulum system. Termed the XY-FP isolator, the new isolation device consists of two orthogonal opposing concave beams interconnected through a sliding mechanism that permits tension to develop in the bearing, thereby preventing uplift. Owing to its distinct configuration, the XY-FP isolator possesses unique properties for a seismic isolator, including uplift restraint, decoupling of the bi-directional motion along two orthogonal directions, and capability of providing independent stiffness and energy dissipation along the principal horizontal directions of the bearing. The study concentrates on introducing the concept and establishing the underlying principles of operation of the new XY-FP isolator, formulating the mathematical model for the XY-FP isolator, and presenting its mechanical behaviour through a displacement-control testing program on a single XY-FP isolator.